2022
DOI: 10.3390/ijerph192214928
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Endurance, Strength and Endurance-Strength Training on Glucose and Insulin Homeostasis and the Lipid Profile of Overweight and Obese Subjects: A Systematic Review and Meta-Analysis

Abstract: The most effective type of training to improve cardiometabolic parameters in overweight subjects is unknown. This meta-analysis compared the effect of endurance, strength and combined training on glucose, insulin metabolism and the lipid profile of overweight and obese adults. The Cochrane, PubMed, Scopus and Web of Science databases were searched to identify randomised trials assessing the effect of training intervention on fasting and 2 h glucose and insulin levels, glycated haemoglobin (HbA1c), homeostatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Furthermore, the effects of exercise are modified by age, sex, and health status [36]. Studies of systematic reviews with meta-analyses have indicated that combined training (RT plus aerobic) is the best option for cardiometabolic markers in adults and children [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the effects of exercise are modified by age, sex, and health status [36]. Studies of systematic reviews with meta-analyses have indicated that combined training (RT plus aerobic) is the best option for cardiometabolic markers in adults and children [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of the online exercise protocol was confirmed by a study by Grazioli et al indicating that training conducted remotely can also help improve patients’ quality of life [ 37 ]. In comparison, the effectiveness of combined training in a non-cancer population is indicated by a meta-analysis by Jamka et al, who showed a more favorable effect of such an intervention on glucose and insulin homeostasis and lipid profile [ 38 ]. The effectiveness of home-based intervention during a pandemic was also confirmed by Natalucci et al, who indicated that a 3-month home-based lifestyle intervention focused on a Mediterranean diet and aerobic exercise significantly reduced echocardiographic signs of diastolic dysfunction and improved autonomic function.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ethnicity and hypertensive status may influence BP responses to exercise [ 49 ]. Second, studies have indicated that combined exercise protocols (aerobic plus resistance) produce greater improvements in cardiometabolic profile than individual exercise modalities [ 12 , 13 , 80 ]. Third, the FFQ used in the present study only included the weekly consumption of 12 food groups.…”
Section: Discussionmentioning
confidence: 99%